Development of an application to identify and prevent suicides in SENA apprentices - Castro Llanos, Yaudith Esther
An application is developed with the objective of persuading, providing support, guiding, and accompanying the apprentices of the SENA community about suicidal ideas and behaviors, the idea of ​​developing an application to prevent suicide arises from a survey that was carried out in the community, where we corroborate the problem presented and it was concluded that the application would have a great impact among young people.